Industriebrachen und Kulturblüten - Vom Wert und dem Dilemma von Zwischennutzungen. - Klaus, Philipp (TH Zürich, NSL, 2008)
Der Beitrag geht dem aktuellen Thema der Zwischennutzungen nach, indem er neuere empirische und theoretische Studien aus der Schweiz, aber auch der EU, vorstellt und einzelne Ergebnisse wertet und kommentiert: die Werterhaltung und die Profitabilität der Zwischennutzungen für die Eigentümer, die Rolle der Kreativwirtschaft als Nutzer ehemaliger Industrieareale und ihre volkswirtschaftliche Bedeutung, die Defizite in der Gründungsförderung der Schweiz gegenüber Deutschland und den Niederlanden oder mögliche alternative Investitionen zu den (fehlenden) staatlichen Interventionen.

Abandoned industrial areas are targets for urban regeneration and new uses, such as shopping centers, offices and luxury housing. During the planning process and the search for investors, brownfield sites are let to temporary users. A wide range of artists, cultural entrepreneurs, small businesses and manufacturers settle into the areas. Relatively low rents make the spaces attractive for such activities. Most owners welcome these tenants as they bring in reasonable income as well as investing in the rooms and infrastructure and improving the image of the area with musicals, theatres, etc. Hence, planners, the public and social scientists paid little attention to the value and significance of the interim activities themselves. A recent research project has shown that more than forty percent of the enterprises in such areas belong to the creative industries. The rate of business start-ups is clearly above average and the impact on the local economy is considerable. Innovative activities have a high presence,an avant garde emerges in cultural areas, and future expectations for businesses are good. The dilemma arises when these enterprises come under pressure to leave when the plans for redevelopment and new spaces are ready. As the importance of creative areas for the life and future of a city is now being recognized, the 'straight' path to redevelopment is being reconsidered. Alternative pension funds seem to be one way out of the dilemma.
Brownfields and new cultural milieus: On the value and dilemma of temporary.
Keywords: Stadtentwicklungsplanung; Stadtquartier; Gewerbe; Dienstleistung; Wirtschaftszweig; Standort; Kultur; Nutzungsänderung; Zwischennutzung; Standortmarketing; Stadtentwicklungspolitik; Kreativwirtschaft; Kulturwirtschaft; Industriebrache; Gewerbebau